2014
DOI: 10.2147/ndt.s57189
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the prediction of the effectiveness of paroxetine for patients with major depressive disorder identified using a receiver operating characteristic curve analysis for early response

Abstract: BackgroundWe investigated cutoff values for the early response of patients with major depressive disorder to paroxetine and their sex differences by using a receiver operating characteristic (ROC) curve analysis to predict the effectiveness of paroxetine.MethodsIn total, 120 patients with major depressive disorder were enrolled and treated with 10–40 mg/day paroxetine for 6 weeks; 89 patients completed the protocol. A clinical evaluation using the Montgomery–Asberg Depression Rating Scale (MADRS) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Many previous studies reported sex differences in the prevalence and characteristics of depressive state and cognitive impairment, and we previously reported sex differences in the association between the presence of SMCs and depressive symptoms and cognitive function and in the prediction of the effectiveness of treatment for patients with depression. 17 , 24 The investigation of the effects of sex might increase the importance of the present results. Fourth, the reliability of discriminating depressive state from cognitive impairment by Factors 1 and 2 is limited because the correlation coefficient between two factors was 0.587, and Factors 1 and 2 did not show significant associations with cognitive impairment.…”
Section: Limitationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Many previous studies reported sex differences in the prevalence and characteristics of depressive state and cognitive impairment, and we previously reported sex differences in the association between the presence of SMCs and depressive symptoms and cognitive function and in the prediction of the effectiveness of treatment for patients with depression. 17 , 24 The investigation of the effects of sex might increase the importance of the present results. Fourth, the reliability of discriminating depressive state from cognitive impairment by Factors 1 and 2 is limited because the correlation coefficient between two factors was 0.587, and Factors 1 and 2 did not show significant associations with cognitive impairment.…”
Section: Limitationsmentioning
confidence: 78%
“…We previously reported that the presence of SMCs influences depressive symptoms and cognitive functioning. 17 In the present study, we investigated the association between the items of the SMC scale and depressive state and cognitive impairment in community-dwelling people in Japan and identified the items that predict depression and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] We may have identified additional results that are more important as well as useful information for clinical settings by studying the patients via other definitions of early response. First, the sample size was small, and the dropout rate was comparatively large in the study.…”
Section: Discussionmentioning
confidence: 99%
“…17 We also defined responders as those patients with MADRS improvements higher than 50% after 6 weeks of treatment compared with the baseline score. 17 We also defined responders as those patients with MADRS improvements higher than 50% after 6 weeks of treatment compared with the baseline score.…”
Section: Data Analyses and Statisticsmentioning
confidence: 99%
“…There are some previous reports focusing on the same field as ours, in which the number of patients included is ~100. 17 , 18 Although we decided sample size of this study according to those reports described, more appropriate approach for sample size determination should have been adopted.…”
Section: Limitationsmentioning
confidence: 99%